Molecular docking analysis on 16 therapeutic ligands of Ocimum tenuiflorum L. (Tulasi) and their prospects in drug design for COVID-19 - Anantharam, Guruprasad; Geetha, S.; Santhana Pandi, P.; Krithika, N.; Chittibabu, C. V. (Journal of Phytology, 2022)
The PyRx software and Discovery studio were used in the present molecular docking studies of the 16 ligands of Ocimum tenuiflorum L., selected based on their high therapeutic potentials, viz., (E)-6-hydroxy-4,6-dimethylhept-3-en-2-one, Apigenin, Bieugenol, Cirsilineol, Cirsimaritin, β-Caryophyllene epoxide, Dehydrodieugenol B, Eugenol, Ferulaldehyde, Isothymonin, Isothymusin, Linalool, Luteolin, Ocimarin, Rosmarinic acid, and Thymol. Saquinavir was used as a positive control. The binding affinities of the 16 ligands to the main proteases of COVID-19 6LU7 and 6Y2E (critical for viral replication) and their ability to arrest the virus replication were recorded. The binding affinities of the ligands to 6LU7 and 6Y2E ranged from -4.3 and -4.7 kcal/mol (for (E)-6-hydroxy-4,6-dimethylhept-3-en-2-one) to -7.6 (for Rosmarinic acid to both target proteins). While the corresponding values for the control drug Saquinavir were -7.8 and -7.6 respectively. The Rosmarinic acid, in binding with both the proteases (-7.6 and -7.6 kcal/mol) showed six conventional hydrogen bonds, one carbon hydrogen bond (ASP 153 had one conventional hydrogen bond and one carbon hydrogen bond), one Pi-alkyl bond, one Pi-Pi stacked bond, eight van der waals bonds for 6LU7 protease; it formed three conventional hydrogen bonds, two Pi-alkyl bonds, one unfavourable donor – donor bond and 14 van der waals bonds with 6Y2E protease. The control drug – Saquinavir in binding with 6LU7 protease showed 12 van der waals, one alkyl, one Pi-alkyl, one Pi-cation, one Pi-stacked and four conventional hydrogen bonds, which indicates that it has less affinity when compared with Rosmarinic acid. Similarly, the control drug on binding with 6Y2E protease exhibited ten van der waals, four Pi-alkyl, one cation and three hydrogen bonds. The results are in conformity to similar other studies, and herald a promising scope for Rosmarinic acid as lead molecule in the drug discovery for COVID-19.